Epstein-Barr virus, interleukin-10 and multiple sclerosis: A ménage à trois - Schönrich, Günther; Abdelaziz, Mohammed O.; Raftery, Martin J. (Frontiers in Immunology, 2022)
Multiple Sclerosis (MS) is an autoimmune disease that is characterized by inflammation and demyelination of nerve cells. There is strong evidence that Epstein-Barr virus (EBV), a human herpesvirus infecting B cells, greatly increases the risk of subsequent MS. Intriguingly, EBV not only induces human interleukin-10 but also encodes a homologue of this molecule, which is a key anti-inflammatory cytokine of the immune system. Although EBV-encoded IL-10 (ebvIL-10) has a high amino acid identity with its cellular counterpart (cIL-10), it shows more restricted and partially weaker functionality. We propose that both EBV-induced cIL-10 and ebvIL-10 act in a temporally and functionally coordinated manner helping the pathogen to establish latency in B cells and, at the same time, to balance the function of antiviral T cells. As a result, the EBV load persisting in the immune system is kept at a constant but individually different level (set point). During this immunological tug of war between virus and host, however, MS can be induced as collateral damage if the set point is too high. Here, we discuss a possible role of ebvIL-10 and EBV-induced cIL-10 in EBV-driven pathogenesis of MS.